SUBSIDIARITY, REPUBLICANISM, AND THE DIVISION OF POWERS IN CANADA - Kong, Hoi (Revue de droit de l'Université de Sherbrooke, 2015)
The present paper undertakes the normative project of determining what subsidiarity should mean in Canadian constitutional law, and how it should be applied. In this paper, I will argue that subsidiarity should be understood in republican terms, and in furtherance of this special issue’s goal of offering tribute to the constitutional jurisprudence of Justice Deschamps, I will argue that a representative case from her federalism jurisprudence is consistent with a republican interpretation of subsidiarity. Part I sets out the case for interpreting Canadian federalism in republican terms and for arguing that these are relevant for understanding the principle of subsidiarity. In brief, the argument is that the republican idea of non-domination provides a normative standard that enables courts to determine whether the conditions of the principle of subsidiarity are satisfied. Part II turns to demonstrate how a republican application of the subsidiarity principle is evident in the federalism jurisprudence of Justice Deschamps.